Cultural Aspects in the Hallucinations and Delusions of Schizoprenic Patients: An Autobiographical Approach - Subandi M.A.; Idei Swasti; Maryama Nihayah; Pungki Sukamto (Indigenous: Jurnal Ilmiah Psikologi, 2025)
Cultural considerations play a pivotal role in the diagnostic process of mental disorders, underscoring the necessity for clinicians to incorporate a cultural formulation in their assessments, as recommended by the DSM-5. This aligns with the fundamental principle of cultural competence essential for clinicians. This study seeks to investigate and elucidate the content of hallucinations and delusions experienced by psychotic patients of Javanese cultural background. This research used an authobiographical approach in qualitative research. Data for the research were derived from authobiographical source, specifically personal narratives of former patients documented in the book 'Ratu Adil'. Thematic analysis was employed for data analysis. Findings revealed a prevalence of delusional experiences over hallucinations among participants. Delusions and hallucinations frequently contained cultural elements, with Islamic themes being the most prominent, followed by Javanese, Chinese, and global cultural elements. The identified themes in the content of delusions and hallucinations depict manifestations of these cultural influences. In conclusion, this study underscores that the content and themes of delusions and hallucinations represent the participants' internal perceptions, often reflecting the external cultural milieu or environment.